Bordering on neglect: environmental justice in Australian planning - Byrne, J.; MacCallum, Diana (Routledge, 2013)
Australian environmental justice research is limited, with scant planning literature on this topic. The Planning Institute of Australia’s core business omits environmental justice concerns. State and local governments are silent on the matter. Few Australian planners would recognise the term. Yet the basic ideals behind environmental justice underpin the core principles of accessibility, equity, social inclusion and participatory democracy, which, in principle, inform Australian planning policies and practice. In this paper, we begin the important task of crossing the borders of ignorance to engage with environmental justice in Australian planning. We review the United States’ (US) origins of the concept, discuss the processes behind the formation of unjust environmental landscapes (both built and organic) and overview some contemporary Australian environmental justice issues that warrant closer scrutiny. We conclude by charting a research agenda and pointing to potential changes and ways forward for planning practice. In so doing, we seek to bridge borders across history, place, disciplines, scholarship and practice.